Structural models of ribonuclease H domains in reverse transcriptases from retroviruses. - Nakamura, H (1991)
Tertiary models of ribonuclease H (RNase H) domains in reverse transcriptases (RTs) from Moloney murine leukemia virus (MuLV) and human immunodeficiency virus (HIV-1) were built based upon the X-ray structure of RNase H from Escherichia coli (E. coli RNase H). In two models of RT-RNase H domains, not only active site residues but also residues, which construct a hydrophobic core and hydrogen bonds, are located in the same positions as those of E. coli RNase H. The whole backbone structure and the electrostatic molecular surface of MuLV RT-RNase H model are similar to those of E. coli RNase H. On the contrary, HIV-1 RT-RNase H model lacks the third helix and the following loop, resulting no positive charge clusters around the hybrid recognition site. Referring the complex models of RTs with their substrate hybrid, the interaction between DNA-polymerase and RNase H domains in RTs was discussed.